An Imagined Geography - Robert Launay (International Institute of Islamic Thought, 2006)
The civil war in Sierra Leone broke out just as JoAnn D’Alisera arrived with the intention of studying a rural Islamic community. Instead, she eventually decided to study Sierra Leonean Muslims in Washington, DC. Based on her ethnographic research, An Imagined Geography is a sensitive depiction of immigrants who must negotiate their accommodation and allegiance to three separate imagined loci: the United States, in which they live; their Sierra Leonean homeland; and the ummah, the global Islamic community of which they are a part. Much of the book centers on the experiences of five individuals, two men and three women, through whose eyes the author explores the tensions involved in being Muslim and African in the United States. Such a closegrained focus allows her to provide a very visceral depiction of how they live out their religious commitments in their everyday interactions with each other, with other Sierra Leoneans, and with Anglo-Americans. The men, for instance, are particularly apt to choose driving taxis as a career, even though some of them are highly educated and qualified for more prestigious and more remunerative jobs. However, their taxis allow them to construct a religious space that they can decorate with Islamic paraphernalia or keep a supply of religious pamphlets to hand out to interested passengers, and to align themselves with religious time so that they can take prayer breaks and even drive to the mosque to pray. The many women-run hotdog stands provide women with a similar freedom, if admittedly less mobility ...